Serum Dipeptidyl Peptidase 4: A Predictor of Disease Activity and Prognosis in Inflammatory Bowel Disease. Issue 11 (8th January 2020) - Pinto-Lopes, Pedro; Afonso, Joana; Pinto-Lopes, Rui; Rocha, Cátia; Lago, Paula; Gonçalves, Raquel; Tavares De Sousa, Helena; Macedo, Guilherme; Camila Dias, Cláudia; Magro, Fernando
Abstract: Background: Serum dipeptidyl peptidase 4 (DPP-4) has drawn particular interest as a biomarker in inflammatory bowel disease (IBD), as this protease inactivates several peptides that participate in the inflammatory cascade. Methods: Two prospectively recruited cohorts consisting of 195 patients (101 had Crohn's disease [CD] and 94 had ulcerative colitis [UC]) were evaluated using clinical indexes and followed up to assess for treatment escalation. Sixty-eight patients underwent endoscopic evaluation at baseline. In the second cohort of 46 biologically treated patients, treatment response was assessed. Serum DPP-4, C-reactive protein (CRP), and fecal calprotectin levels were quantified at baseline and during follow-up. Results: Median DPP-4 levels were significantly lower in active IBD patients when compared with remitters (CD: 1043 [831–1412] vs 1589 [1255–1956] ng/mL; P < 0.001; UC: 1317 [1058–1718] vs 1798 [1329–2305] ng/mL; P = 0.001) and healthy controls (2175 [1875–3371] ng/mL). In fact, DPP-4 was able to distinguish clinical and endoscopic activity from remission, with areas under the curve (AUC) of 0.81/0.93 (CD) and 0.71/0.79 (UC), along with the need for treatment escalation, with comparable AUCs of 0.79 (CD) and 0.77 (UC). Furthermore, DPP-4 levels were higher in responders to treatment and more pronounced among UC (1467 [1301–1641] vs 1211 [1011–1448] ng/mL; P < 0.001) than CD patients (1385 [1185–1592] vs 1134 [975–1469] ng/mL; P = 0.015). Conclusions: Our results suggest that serum DPP-4 can be used as a noninvasive biomarker of IBD activity and biological treatment response and a predictor of treatment escalation, particularly when combined with other biomarkers. Abstract : Serum dipeptidyl peptidase 4 has drawn particular interest due to observations of altered expression profiles in patients with inflammatory bowel disease (IBD). Our study concludes that it can be used as a noninvasive biomarker of IBD activity and biological treatment response and a predictor of treatment escalation. Video Abstract: